2020
DOI: 10.1038/s41598-020-74061-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of multiclass endocrine disrupting compounds in a drinking water supply system and associated risks

Abstract: Contamination by endocrine disrupting compounds (EDCs) concerns the security and sustainability of a drinking water supply system and human exposure via water consumption. This study analyzed the selected EDCs in source (river water, n = 10) and supply (tap water, n = 155) points and the associated risks. A total of 14 multiclass EDCs was detected in the drinking water supply system in Malaysia. Triclosan (an antimicrobial agent) and 4-octylphenol (a plasticizer) were only detected in the tap water (up to 9.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…The DWTP is the last stage of EDCs exposure between the drinking water supply and the consumers. However, standard drinking water treatment facilities are insufficient for eliminating these pollutants, resulting in their dissemination into the drinking water supply 17 . Despite of the extensive use and prevalence of plasticizers in the environment, developing countries like India still lack the awareness and strict guidelines on environmental monitoring of these pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The DWTP is the last stage of EDCs exposure between the drinking water supply and the consumers. However, standard drinking water treatment facilities are insufficient for eliminating these pollutants, resulting in their dissemination into the drinking water supply 17 . Despite of the extensive use and prevalence of plasticizers in the environment, developing countries like India still lack the awareness and strict guidelines on environmental monitoring of these pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the countries,natural reservoirs such asrivers, lakes, dams, etc are the primary source fordrinking water treatment plant (DWTP). Direct sources, such as untreated and treated discharges and indirect sources such as runoff and leachates are the two main causes of EDCs contamination in surface water.Between the drinking water source and the consumers, the DWTP is the last point of exposure for EDCs and unfortunatelythe traditional drinking water treatment facilities are insu cient for eliminating these pollutants, resulting in theirdisseminationin the drinking water supply 14 . Despite of the extensive use and prevalence of plasticizers in the environment, developing countries like India still lack the awareness and strict guidelines on environmental monitoring of these pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the recalcitrant physicochemical properties of PPCPs, a complete removal of PPCPs by conventional wastewater treatment processes is not feasible and thereby their presence in drinking water poses a potential threat to aquatic life and public health (Snyder 2008;Wee et al, 2020). It has been reported that PPCPs and their secondary metabolites are biologically active and they can be accumulated in aquatic organisms especially in fish (Ebele et al, 2017;Muir et al, 2017;Yin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%